A case of WAGR syndrome in association with developmental glaucoma requiring bilateral Baerveldt glaucoma implants and subsequent tube repositioning - Akagi T; Yoshikawa M; Nakanishi H; Yoshimura N (Clinical Ophthalmology, 2015)
Tadamichi Akagi, Munemitsu Yoshikawa, Hideo Nakanishi, Nagahisa Yoshimura Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Japan Abstract: Glaucoma drainage device implantation is efficacious for the treatment of pediatric glaucoma patients when multiple angle surgeries fail. However, tube touching of the corneal endothelium is one of the major postoperative complications to deal with. A 15-month-old male patient with Wilms’ tumor, aniridia, genitourinary anomalies, and mental retardation (WAGR) syndrome was diagnosed with bilateral developmental glaucoma. He underwent Baerveldt glaucoma implant (BGI) surgeries in both eyes after multiple failed trabeculotomies. The tube in his right eye was touching the cornea 15 months after BGI surgery. To avoid corneal endothelium damage, BGI tube repositioning with scleral fixation was performed without serious complications. The bilateral BGI surgeries achieved successful intraocular pressure reduction for over 2 years and tube repositioning with scleral fixation of BGI tube was successful for BGI tube malposition. Although careful attention to intraocular pressure and tube malposition is essential after glaucoma drainage device implantation, especially in pediatric cases, BGI surgery is effective in the management of developmental glaucoma following unsuccessful angle surgeries. Keywords: Baerveldt glaucoma implant, developmental glaucoma, WAGR syndrome, tube repositioning, glaucoma drainage device